A high specific capacity composite material, its preparation method and application

By using Co2MnO4.5@Ti3C2 composite material in supercapacitors, the problems of metal oxide volume change and two-dimensional material aggregation are solved, high specific surface area and conductivity are achieved, capacity and cycling stability are improved, and good The ion transmission channel becomes the ideal supercapacitor material.

CN114883115BActive Publication Date: 2024-12-27净海新能源科技创新(镇江)有限公司 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210390152.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-14
Publication Date
2024-12-27
Estimated Expiration
2042-04-14

AI Technical Summary

Technical Problem

The volume of metal oxides changes dramatically during charging and discharging in supercapacitors, resulting in poor conductivity and electrochemical activity. Two-dimensional materials such as Ti3C2 nanosheets are prone to aggregation, reducing the active surface area, and unable to fully exert electrochemical properties.

Method used

Co2MnO4.5@Ti3C2 composite material was used to prepare Co2MnO4.5 nano-hollow spheres by hydrothermal method and insert them between Ti3C2 (MXene) nanosheets to prevent the secondary stacking of nanosheets, build a stable structure, increase the specific surface area and Inhibit the volume change of Co2MnO4.5 nano-open spheres in redox reaction.

Benefits of technology

The Co2MnO4.5@Ti3C2 composite material with high specific surface area and high conductivity is realized, providing good ion transmission channels, preventing nanosheets from aggregating, improving capacitance and cycling stability, making it an ideal supercapacitor material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114883115B_ABST
    Figure CN114883115B_ABST
Patent Text Reader

Abstract

The invention discloses a composite material with high specific capacity and a preparation method and application thereof. The composite material is Co2MnO 4.5 @Ti3C2, made of Co2MnO 4.5 Nano hollow spheres and Ti3C2 (MXene) nanosheets. Co2MnO 4.5 Nano hollow spheres and Ti3C2 (MXene) nanosheets, and then Co2MnO 4.5 The hollow nanospheres are inserted between Ti3C2 (MXene) nanosheets. 4.5 The Ti3C2 composite material has a large specific surface area and high electrical conductivity, which can provide a good ion transport channel. Due to its special structure, it can prevent the restacking of MXene nanosheets and the deposition of Co2MnO 4.5 The volume of the nano hollow spheres changes dramatically; at the same time, the composite material has high capacitance and high cycle stability, making it an ideal material for supercapacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a Co2MnO 4.5 @Ti3C2 composite material and its preparation method and application belong to the field of supercapacitor materials. Background Art

[0002] Cobalt-based and manganese-based oxides have low cost, good conductivity, large specific surface area, excellent redox activity, and high theoretical capacitance (Co3O4~3560F g -1 ,MnO2~1370F g -1 ) and low toxicity. In addition, cobalt has a high oxidation potential and manganese has excellent electron mobility, making cobalt-based and manganese-based oxides very promising electrode materials. However, there are still some problems in the application of metal oxides in supercapacitors. Because during the charging and discharging process, the volume of metal oxides changes dramatically, resulting in poor conductivity and electrochemical activity.

[0003] MXenes are similar to graphene materials and are accordion-shaped. They are considered to be a promising supercapacitor electrode material due to their unique two-dimensional flake morphology, rich surface groups and excellent conductivity. x Due to its simple synthesis process, high aspect ratio and excellent electrical conductivity (~6500S cm -1 ) and has broad application prospects. However, as a typical two-dimensional material similar to graphene, ultrathin nanosheets have high surface energy and a strong tendency to aggregate due to the van der Waals forces between nanosheets, which will reduce the active surface area and lead to insufficient utilization of active sites, making it unable to fully exert its electrochemical performance. Therefore, it is urgent to design a composite material with good conductivity and electrochemical activity, high capacitance and high cycle stability. Summary of the invention

[0004] Objective of the invention: The first objective of the present invention is to provide a Co2MnO 4.5 @Ti3C2 composite material; the second object of the present invention is to provide a method for preparing the composite material; the third object of the present invention is to provide an application of the composite material in the preparation of a supercapacitor.

[0005] Technical solution: The present invention provides a composite material with high specific capacity, which is Co2MnO 4.5 @Ti3C2, which is composed of Co2MnO 4.5 Nano hollow spheres and Ti3C2 (MXene) nanosheets, the Co2MnO 4.5 The hollow nanospheres are inserted between the Ti3C2 (MXene) nanosheets.

[0006] The high specific capacity Co2MnO 4.5 The preparation method of the Ti3C2 composite material comprises the following steps:

[0007] (1) Using carbon spheres as templates, tetrahydrated cobalt acetate and tetrahydrated manganese acetate as cobalt sources and manganese sources, a mixed solution was prepared by a hydrothermal method, the mixed solution was centrifuged and washed with water for multiple times, dried, and calcined in an air atmosphere to obtain Co2MnO 4.5 Hollow nanospheres;

[0008] (2) dissolving lithium fluoride (LiF) in hydrochloric acid to prepare an etching solution, slowly adding Ti3AlC2 powder to the etching solution, heating for reaction, centrifugal washing, and freeze-drying to obtain MXene nanosheets;

[0009] (3) Co2MnO 4.5 The hollow nanospheres were ultrasonically mixed with MXene nanosheets and freeze-dried to obtain Co2MnO 4.5 @Ti3C2 composite material.

[0010] Wherein, in step (1), the mass ratio of cobalt acetate tetrahydrate to manganese acetate tetrahydrate is 1-1.1:1.

[0011] Wherein, in step (1), the hydrothermal method is to react at 90-100° C. for 7-8 hours.

[0012] Wherein, in step (1), the drying is carried out at 70-80° C. for 12-16 hours.

[0013] Wherein, in step (1), the calcination is carried out at 450-500° C. for 2-3 hours.

[0014] Wherein, in step (2), the solid-liquid ratio of LiF to hydrochloric acid is 80-100:1 mg / ml.

[0015] Wherein, in step (2), the mass ratio of LiF to Ti3AlC2 powder is 8:3-5.

[0016] Wherein, in step (2), the time for slow addition is 5 to 15 minutes.

[0017] Wherein, in step (2), the heating reaction is carried out at 30-40° C. for 24-36 hours.

[0018] Wherein, in step (3), Co2MnO 4.5 The hollow nanospheres and MXene nanosheets were added to the ethylene glycol solution in a mass ratio of 10:2 to 5 and ultrasonically mixed.

[0019] Wherein, in step (3), the ultrasonic mixing time is 1.5 to 3 hours, and the power during ultrasonic mixing is 180 to 250 W.

[0020] The high specific capacity Co2MnO 4.5 @Application of Ti3C2 composite materials in the preparation of supercapacitors.

[0021] The present invention adopts Co2MnO 4.5 Co2MnO prepared by hollow nanospheres and Ti3C2(MXene) nanosheets 4.5 @Ti3C2 composite material, Co2MnO 4.5 The hollow nanospheres are inserted between the MXene nanosheets, preventing the secondary stacking of the MXene nanosheets, constructing a stable new structure, and increasing the specific surface area of ​​the composite material. 4.5 The dramatic change in volume of hollow nanospheres during redox reactions.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: Co2MnO 4.5 @Ti3C2 composite material is composed of Co2MnO 4.5 The nano hollow spheres and Ti3C2 (MXene) nanosheets have large specific surface area, high conductivity, and can provide a good ion transport channel. Due to its special structure, it can prevent the secondary accumulation of MXene nanosheets and the formation of Co2MnO 4.5 The volume of the hollow nanospheres changes dramatically during the redox reaction; at the same time, the composite material has high capacitance and high cycle stability, making it an ideal material for supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Co2MnO prepared in Example 1 4.5 Transmission electron microscopy image of hollow nanospheres;

[0024] Figure 2 Co2MnO prepared in Example 1 4.5 @TEM image of Ti3C2 composite material;

[0025] Figure 3 Co2MnO prepared in Example 1 4.5 @Cyclic voltammetry curve of Ti3C2 composite material;

[0026] Figure 4 Co2MnO prepared in Example 1 4.5 @Charge and discharge curve of Ti3C2 composite material;

[0027] Figure 5Co2MnO prepared in Example 2 4.5 @Cyclic voltammetry curve of Ti3C2 composite material;

[0028] Figure 6 Co2MnO prepared in Example 2 4.5 @Charge and discharge curve of Ti3C2 composite material;

[0029] Figure 7 Co2MnO prepared in Example 3 4.5 @Cyclic voltammetry curve of Ti3C2 composite material;

[0030] Figure 8 Co2MnO prepared in Example 3 4.5 @Charge and discharge curve of Ti3C2 composite material;

[0031] Fig. 9 Co2MnO prepared in Example 4 4.5 @Cyclic voltammetry curve of Ti3C2 composite material;

[0032] Fig.10 Co2MnO prepared in Example 4 4.5 @Charge and discharge curve of Ti3C2 composite material;

[0033] Fig.11 Co2MnO prepared in Example 5 4.5 @Cyclic voltammetry curve of Ti3C2 composite material;

[0034] Fig.12 Co2MnO prepared in Example 5 4.5 @Charge and discharge curve of Ti3C2 composite material;

[0035] Fig.13 Co2MnO prepared for Comparative Examples 1, 2 and Example 1 4.5 Cyclic voltammetry curve of hollow nanospheres;

[0036] Fig.14 Co2MnO prepared for Comparative Examples 1, 2 and Example 1 4.5 Charge and discharge curves of hollow nanospheres;

[0037] Fig.15 Cyclic voltammetry curves of the composite materials prepared in Comparative Example 3 and Example 1;

[0038] Fig.16 The charge and discharge curves of the composite materials prepared in Comparative Example 3 and Example 1 are shown. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0040] The raw materials used in the present invention can all be purchased from the market.

[0041] Example 1

[0042] Ensure that the production area and equipment are clean and dry, and clean and disinfect the utensils used.

[0043] 1. Preparation of Co2MnO with high specific capacitance 4.5 @Ti3C2 composite material:

[0044] (1) Co2MnO 4.5 Preparation of hollow nanospheres: Weigh 0.0935g of tetrahydrated cobalt acetate and 0.0925g of tetrahydrated manganese acetate and add them to a flask, then measure 30mL of deionized water and add them, then weigh 60mg of carbon ball powder and add it to the solution, ultrasonicate and stir for 30min each to form a uniform suspension. Then weigh 1.25g of urea and add it to the suspension, continue stirring for 30min, and stir the reaction in a 90℃ oil bath for 8h. After the reaction is completed, wash with deionized water and dry at 80℃ for 12h. Finally, heat to 450℃ in an air atmosphere and keep warm for 2h to obtain Co2MnO 4.5 Hollow nanospheres;

[0045] (2) First, measure 10mL of the prepared 9mol / L hydrochloric acid solution and add it to a polytetrafluoroethylene beaker. Then weigh 0.8g of lithium fluoride powder and slowly add the powder to the hydrochloric acid solution. Stir continuously for 10 minutes to prepare an etchant. Next, weigh 0.5g of MAX (Ti3AlC2) powder and slowly add it to the etchant within 5 minutes. Continue stirring the reaction at 40°C for 24 hours. After the reaction is completed, wash with deionized water. When the pH is about 6, collect the precipitate, then add deionized water to disperse the precipitate, and then place the dispersed solution under N2 protection for ultrasonic treatment for 60 minutes. Finally, collect the dark green upper layer of well-dispersed liquid, dry it by freeze-drying, and finally obtain the prepared MXene (Ti3C2) powder.

[0046] (3) First, 30 mL of dimethyl sulfoxide solution (DMSO) was weighed into a flask, and then 6 mg of Ti3C2 powder was added to the solution. Ultrasonication and stirring were performed to mix the solution thoroughly. Then, 20 mg of Co2MnO 4.5 Nano hollow sphere nano hollow sphere powder is mixed thoroughly, and then the mixed solution is ultrasonicated at 250W power for 2h under nitrogen protection. Finally, the product after the reaction is collected and freeze-dried to obtain Co2MnO 4.5 @Ti3C2 composite material.

[0047] The Co2MnO prepared in this example 4.5 Hollow nanospheres, Co2MnO 4.5 @Ti3C2 composite material was analyzed by transmission electron microscopy, and the results are as follows Figure 1 and Figure 2 As shown, Figure 1 Co2MnO prepared in Example 1 4.5 Transmission electron microscopy image of hollow nanospheres; Figure 2 Co2MnO prepared in Example 1 4.5 @ Transmission electron microscope image of Ti3C2 composite material. Figure 1 and Figure 2 It can be seen that Co2MnO 4.5 The hollow nanospheres were introduced into the Ti3C2 nanosheets, which increased the specific surface area of ​​the material, inhibited the agglomeration of the Ti3C2 nanosheets, and protected the Co2MnO 4.5 The rapid change in volume during the charging and discharging process can also provide a better ion transmission channel and enhance the conductivity of the material.

[0048] The Co2MnO prepared in this example 4.5 The electrochemical performance of the Ti3C2 composite material was tested and analyzed using a traditional three-electrode system (cyclic voltammetry and charge-discharge tests were performed using a Chenhua electrochemical workstation, the electrolyte solution was 6 mol / L KOH solution, the prepared composite material was used as the working electrode, the platinum sheet was used as the counter electrode, the mercury / mercury oxide electrode was used as the reference electrode, and the test temperature was 25°C). The results are as follows Figure 3 and Figure 4 As shown. Figure 3 Co2MnO prepared in Example 1 4.5 @Cyclic voltammetry curve of Ti3C2 composite material; Figure 3 It can be seen that the CV curve has a pair of obvious redox peaks, indicating that the synthesized material has obvious Faraday pseudocapacitance characteristics. Figure 4 Co2MnO prepared in Example 1 4.5 @Charge and discharge curve of Ti3C2 composite material; Figure 4 It can be seen that Co2MnO 4.5 @Ti3C2 composite material has a specific capacitance of 1564F / g at 1A / g, and the prepared Co2MnO 4.5 @Ti3C2 composite materials have excellent electrochemical properties.

[0049] Example 2

[0050] (1) Co2MnO 4.5Preparation of hollow nanospheres: Weigh 0.0935g of tetrahydrated cobalt acetate and 0.0935g of tetrahydrated manganese acetate and add them to a flask, then measure 30mL of deionized water and add them, then weigh 60mg of carbon ball powder and add it to the solution, ultrasonicate and stir for 30min each to form a uniform suspension. Then weigh 1.25g of urea and add it to the suspension, continue stirring for 30min, and stir the reaction in a 100℃ oil bath for 7h. After the reaction is completed, wash with deionized water and dry at 70℃ for 16h. Finally, heat to 500℃ in an air atmosphere and keep warm for 2h to obtain Co2MnO 4.5 Hollow nanospheres;

[0051] (2) First, measure 10mL of the prepared 9mol / L hydrochloric acid solution and add it to a polytetrafluoroethylene beaker. Then weigh 0.8g of lithium fluoride powder and slowly add the powder to the hydrochloric acid solution. Stir continuously for 10 minutes to prepare an etchant. Next, weigh 0.5g of MAX (Ti3AlC2) powder and slowly add it to the etchant within 5 minutes. Continue stirring the reaction at 30°C for 36 hours. After the reaction is completed, wash with deionized water. When the pH is about 6, collect the precipitate, then add deionized water to disperse the precipitate, and then place the dispersed solution under N2 protection for ultrasonic treatment for 60 minutes. Finally, collect the dark green upper layer of well-dispersed liquid, dry it by freeze-drying, and finally obtain the prepared MXene (Ti3C2) powder.

[0052] (3) First, 30 mL of dimethyl sulfoxide solution (DMSO) was weighed into a flask, and then 4 mg of Ti3C2 powder was weighed and added to the solution. Ultrasonication and stirring were performed to mix the mixture thoroughly. Then, 20 mg of Co2MnO 4.5 Nano hollow sphere nano hollow sphere powder is mixed thoroughly, and then the mixed solution is ultrasonicated at 180W power for 1.5h under nitrogen protection. Finally, the product after the reaction is collected and freeze-dried to obtain Co2MnO 4.5 @Ti3C2 composite material.

[0053] The Co2MnO prepared in this example 4.5 The electrochemical performance of the Ti3C2 composite material was tested and analyzed. The test analysis was the same as in Example 1. The results are as follows Figure 5 and Figure 6 As shown, Figure 5 Co2MnO prepared in Example 2 4.5 @Cyclic voltammetry curve of Ti3C2 composite material; Figure 5 It can be seen that the CV curve has a pair of obvious redox peaks, indicating that the synthesized material has obvious Faraday pseudocapacitance characteristics. Figure 6Co2MnO prepared in Example 2 4.5 @Charge and discharge curve of Ti3C2 composite material; Figure 6 It can be seen that Co2MnO 4.5 @Ti3C2 composite material has a specific capacitance of 1115F / g at 1A / g, and the prepared Co2MnO 4.5 @Ti3C2 composite materials have good electrochemical properties.

[0054] Example 3

[0055] (1) Co2MnO 4.5 Preparation of hollow nanospheres: Weigh 0.0935g of tetrahydrated cobalt acetate and 0.085g of tetrahydrated manganese acetate and add them to a flask, then measure 30mL of deionized water and add them, then weigh 60mg of carbon ball powder and add it to the solution, ultrasonicate and stir for 30min each to form a uniform suspension. Then weigh 1.25g of urea and add it to the suspension, continue stirring for 30min, and stir the reaction in a 90℃ oil bath for 8h. After the reaction is completed, wash with deionized water and dry at 80℃ for 14h. Finally, heat to 450℃ in an air atmosphere and keep warm for 3h to obtain Co2MnO 4.5 Hollow nanospheres;

[0056] (2) First, measure 10mL of the prepared 9mol / L hydrochloric acid solution and add it to a polytetrafluoroethylene beaker. Then weigh 0.8g of lithium fluoride powder and slowly add the powder to the hydrochloric acid solution. Stir continuously for 10 minutes to prepare an etchant. Next, weigh 0.5g of MAX (Ti3AlC2) powder and slowly add it to the etchant within 5 minutes. Continue stirring the reaction at 40°C for 24 hours. After the reaction is completed, wash with deionized water. When the pH is about 6, collect the precipitate, then add deionized water to disperse the precipitate, and then place the dispersed solution under N2 protection for ultrasonic treatment for 60 minutes. Finally, collect the dark green upper layer of well-dispersed liquid, dry it by freeze-drying, and finally obtain the prepared MXene (Ti3C2) powder.

[0057] (3) First, 30 mL of dimethyl sulfoxide solution (DMSO) was weighed into a flask, and then 8 mg of Ti3C2 powder was weighed and added to the solution. Ultrasonication and stirring were performed to mix the mixture thoroughly. Then, 20 mg of Co2MnO 4.5 Nano hollow sphere nano hollow sphere powder is mixed thoroughly, and then the mixed solution is ultrasonicated at 250W power for 2.5h under nitrogen protection. Finally, the product after the reaction is collected and freeze-dried to obtain Co2MnO 4.5 @Ti3C2 composite material.

[0058] The Co2MnO prepared in this example 4.5 The electrochemical performance of the Ti3C2 composite material was tested and analyzed. The test analysis was the same as in Example 1. The results are as follows Figure 7 and Figure 8 shown. Figure 7 Co2MnO prepared in Example 3 4.5 @Cyclic voltammetry curve of Ti3C2 composite material; Figure 7 It can be seen that the CV curve has a pair of obvious redox peaks, indicating that the synthesized material has obvious Faraday pseudocapacitance characteristics. Figure 8 Co2MnO prepared in Example 3 4.5 @Charge and discharge curve of Ti3C2 composite material; Figure 8 It can be seen that Co2MnO 4.5 @Ti3C2 composite material has a specific capacitance of 1376F / g at 1A / g, and the prepared Co2MnO 4.5 @Ti3C2 composite materials have good electrochemical properties.

[0059] Example 4

[0060] (1) Co2MnO 4.5 Preparation of hollow nanospheres: Weigh 0.0935g of tetrahydrated cobalt acetate and 0.085g of tetrahydrated manganese acetate and add them to a flask, then measure 30mL of deionized water and add them, then weigh 60mg of carbon ball powder and add it to the solution, ultrasonicate and stir for 30min each to form a uniform suspension. Then weigh 1.25g of urea and add it to the suspension, continue stirring for 30min, and stir the reaction in a 90℃ oil bath for 8h. After the reaction is completed, wash with deionized water and dry at 80℃ for 14h. Finally, heat to 450℃ in an air atmosphere and keep warm for 2h to obtain Co2MnO 4.5 Hollow nanospheres;

[0061] (2) First, measure 10mL of the prepared 9mol / L hydrochloric acid solution and add it to a polytetrafluoroethylene beaker. Then weigh 0.8g of lithium fluoride powder and slowly add the powder to the hydrochloric acid solution. Stir continuously for 10 minutes to prepare an etchant. Next, weigh 0.5g of MAX (Ti3AlC2) powder and slowly add it to the etchant within 5 minutes. Continue stirring the reaction at 40°C for 24 hours. After the reaction is completed, wash with deionized water. When the pH is about 6, collect the precipitate, then add deionized water to disperse the precipitate, and then place the dispersed solution under N2 protection for ultrasonic treatment for 60 minutes. Finally, collect the dark green upper layer of well-dispersed liquid, dry it by freeze-drying, and finally obtain the prepared MXene (Ti3C2) powder.

[0062] (3) First, 30 mL of dimethyl sulfoxide solution (DMSO) was weighed into a flask, and then 10 mg of Ti3C2 powder was weighed and added to the solution. Ultrasonication and stirring were performed to mix the mixture thoroughly. Then, 20 mg of Co2MnO 4.5 Nano hollow sphere nano hollow sphere powder is mixed thoroughly, and then the mixed solution is ultrasonicated at 250W power for 3h under nitrogen protection.

[0063] The Co2MnO prepared in this example 4.5 The electrochemical performance of the Ti3C2 composite material was tested and analyzed. The test analysis was the same as in Example 1. The results are as follows Fig. 9 and Fig.10 shown. Fig. 9 Co2MnO prepared in Example 4 4.5 @Cyclic voltammetry curve of Ti3C2 composite material; Fig. 9 It can be seen that the CV curve has a pair of obvious redox peaks, indicating that the synthesized material has obvious Faraday pseudocapacitance characteristics. Fig.10 Co2MnO prepared in Example 4 4.5 @Charge and discharge curve of Ti3C2 composite material; Fig.10 It can be seen that Co2MnO 4.5 @Ti3C2 composite material has a specific capacitance of 1228F / g at 1A / g, and the prepared Co2MnO 4.5 @Ti3C2 composite materials have good electrochemical properties.

[0064] Example 5

[0065] (1) Co2MnO 4.5 Preparation of hollow nanospheres: Weigh 0.0935g of tetrahydrated cobalt acetate and 0.0925g of tetrahydrated manganese acetate and add them to a flask, then measure 30mL of deionized water and add them, then weigh 60mg of carbon ball powder and add it to the solution, ultrasonicate and stir for 30min each to form a uniform suspension. Then weigh 1.25g of urea and add it to the suspension, continue stirring for 30min, and stir the reaction in a 90℃ oil bath for 8h. After the reaction is completed, wash with deionized water and dry at 80℃ for 12h. Finally, heat to 450℃ in an air atmosphere and keep warm for 2h to obtain Co2MnO 4.5 Hollow nanospheres;

[0066] (2) First, measure 10mL of the prepared 9mol / L hydrochloric acid solution and add it to a polytetrafluoroethylene beaker. Then weigh 0.8g of lithium fluoride powder and slowly add the powder to the hydrochloric acid solution. Stir continuously for 10 minutes to prepare an etchant. Next, weigh 0.5g of MAX (Ti3AlC2) powder and slowly add it to the etchant within 5 minutes. Continue stirring the reaction at 30°C for 24 hours. After the reaction is completed, wash with deionized water. When the pH is about 6, collect the precipitate, then add deionized water to disperse the precipitate, and then place the dispersed solution under N2 protection for ultrasonic treatment for 60 minutes. Finally, collect the dark green upper layer of well-dispersed liquid, dry it by freeze-drying, and finally obtain the prepared MXene (Ti3C2) powder.

[0067] (3) First, 30 mL of dimethyl sulfoxide solution (DMSO) was weighed into a flask, and then 6 mg of Ti3C2 powder was weighed and added to the solution. Ultrasonication and stirring were performed to mix the mixture thoroughly. Then, 20 mg of Co2MnO 4.5 Nano hollow sphere nano hollow sphere powder is mixed thoroughly, and then the mixed solution is ultrasonicated at 250W power for 2h under nitrogen protection. Finally, the product after the reaction is collected and freeze-dried to obtain Co2MnO 4.5 @Ti3C2 composite material.

[0068] The Co2MnO prepared in this example 4.5 The electrochemical performance of the Ti3C2 composite material was tested and analyzed. The test analysis was the same as in Example 1. The results are as follows Fig.11 shown. Fig.11 Co2MnO prepared in Example 5 4.5 @Cyclic voltammetry curve of Ti3C2 composite material; Fig.11 It can be seen that the CV curve has a pair of obvious redox peaks, indicating that the synthesized material has obvious Faraday pseudocapacitance characteristics. Fig.12 Co2MnO prepared in Example 5 4.5 @Charge and discharge curve of Ti3C2 composite material; Fig.12 It can be seen that Co2MnO 4.5 @Ti3C2 composite material has a specific capacitance of 1240F / g at 1A / g, and the prepared Co2MnO 4.5 @Ti3C2 composite materials have good electrochemical properties.

[0069] Comparative Example 1

[0070] This comparative example prepares Co2MnO 4.5The method of preparing hollow nanospheres comprises the following steps: weighing 0.00935 g of tetrahydrated cobalt acetate and 0.000925 g of tetrahydrated manganese acetate and adding them to a flask, then measuring 30 mL of deionized water and adding them thereto, and then weighing 60 mg of carbon ball powder and adding them to the solution, ultrasonicating and stirring for 30 min each to form a uniform suspension. Then weighing 1.25 g of urea and adding it to the suspension, stirring for another 30 min, and stirring the reaction in a 90 ° C oil bath for 8 h. After the reaction is completed, washing with deionized water and drying at 80 ° C for 12 h. Finally, heating to 450 ° C in an air atmosphere and keeping it warm for 2 h to obtain Co2MnO 4.5 Hollow nanospheres;

[0071] Comparative Example 2

[0072] This comparative example prepares Co2MnO 4.5 The method of preparing hollow nanospheres comprises the following steps: weighing 0.187 g of tetrahydrated cobalt acetate and 0.185 g of tetrahydrated manganese acetate and adding them to a flask, then measuring 30 mL of deionized water and adding them thereto, and then weighing 60 mg of carbon ball powder and adding them to the solution, ultrasonicating and stirring for 30 min each to form a uniform suspension. Then weighing 1.25 g of urea and adding it to the suspension, stirring for another 30 min, and stirring the reaction in a 90 ° C oil bath for 8 h. After the reaction is completed, wash with deionized water and dry at 80 ° C for 12 h. Finally, the temperature is raised to 450 ° C in an air atmosphere and kept for 2 h to obtain Co2MnO 4.5 Hollow nanospheres;

[0073] The Co2MnO prepared in Example 1, Comparative Example 1 and Comparative Example 2 4.5 The electrochemical performance of the hollow nanospheres was tested and analyzed in the same manner as in Example 1. Fig.13 Shown and Fig.14 shown. Fig.13 Co2MnO prepared in Comparative Examples 1, 2 and Examples 4.5 Cyclic voltammetry curve of hollow nanospheres; Fig.13 It can be seen that the CV curves have a pair of obvious redox peaks, indicating that the synthesized material has obvious Faraday pseudocapacitive characteristics, and the CV curve area of ​​Example 1 is the largest, indicating that it has the best energy storage performance. Fig.14 Co2MnO prepared in Comparative Examples 1, 2 and Example 1 4.5 The charge and discharge curve of hollow nanospheres. Fig.14 It can be seen that the Co2MnO prepared in Example 1 4.5 The discharge time of the nano hollow spheres is much longer than that of Comparative Examples 1 and 2, indicating that it has the best energy storage performance.

[0074] Comparative Example 3

[0075] Co2MnO4.5 Preparation of hollow nanospheres: Weigh 0.0935g of cobalt acetate tetrahydrate and 0.0925g of manganese acetate tetrahydrate and add them to a flask, then measure 30mL of deionized water and add them, ultrasonically stir to fully dissolve them. Then weigh 60mg of carbon ball powder and add it to the solution, ultrasonically and stir for 30min each to form a uniform suspension. Then weigh 1.25g of urea and add it to the suspension, continue stirring for 30min, and stir the reaction in a 90℃ oil bath for 8h. After the reaction is completed, cool to room temperature, wash with deionized water, and dry at 80℃ for 12h. Finally, heat to 450℃ in an air atmosphere and keep warm for 2h to obtain Co2MnO 4.5 Nano hollow spheres. Weigh 6 mg of graphene powder and 20 mg of Co2MnO 4.5 The powder was reacted at 190 °C for 12 h by a hydrothermal method and then calcined at 500 °C in nitrogen for 3 h to prepare Co2MnO 4.5 @Graphene composites.

[0076] The obtained Co2MnO 4.5 @ The graphene composite material was tested and analyzed for electrochemical performance. The test analysis was the same as in Example 1. The results are as follows Fig.15 and Fig.16 shown. Fig.15 The cyclic voltammetry curves of the composites prepared in Comparative Example 3 and Example 1 are shown in FIG. Fig.15 It can be seen that the CV curves have a pair of obvious redox peaks, indicating that the synthesized material has obvious Faraday pseudocapacitive characteristics, and the CV curve area of ​​Example 1 is the largest, indicating that it has the best energy storage performance. Fig.16 The charge and discharge curves of the composite materials prepared in Comparative Example 3 and Example 1 are shown in FIG. Fig.16 It can be seen that Co2MnO 4.5 The discharge time of the composite material of nano hollow spheres and Ti3C2 is longer than that of the graphene composite material, indicating that Co2MnO 4.5 @Ti3C2 has better energy storage performance.

Claims

1. A composite material with high specific capacity, characterized in that: The composite material is Co2MnO 4.5 @Ti3C2,Co2MnO 4.5 @Ti3C2 is made of Co2MnO 4.5 Nano hollow spheres and Ti3C2 nanosheets, the Co2MnO 4.5 The preparation method of the composite material with high specific capacity by inserting the nano hollow spheres between Ti3C2 nano sheets comprises the following steps: (1) Using carbon spheres as templates, tetrahydrated cobalt acetate and tetrahydrated manganese acetate were used as cobalt and manganese sources, respectively, to prepare a mixed solution by a hydrothermal method. The mixed solution was centrifuged and washed with water for multiple times, dried, and calcined in an air atmosphere to obtain Co2MnO 4.5 Hollow nanospheres; the mass ratio of cobalt acetate tetrahydrate to manganese acetate tetrahydrate is 1-1.1:1, and the mass ratio of manganese acetate tetrahydrate to carbon ball powder is 93.5:60, 92.5:60 or 85:60; (2) LiF is dissolved in hydrochloric acid to prepare an etching solution, Ti3AlC2 powder is slowly added to the etching solution, heated for reaction, centrifuged for washing, and freeze-dried to obtain Ti3C2 nanosheets; the slow addition time is 5-15 min, and the heating reaction is carried out at 30-40 °C for 24-36 h; (3) Co2MnO 4.5 Nano hollow spheres were ultrasonically mixed with Ti3C2 nanosheets and freeze-dried to obtain Co2MnO 4.5 @Ti3C2 composite material, Co2MnO 4.5 The hollow nanospheres and Ti3C2 nanosheets were added to the ethylene glycol solution in a mass ratio of 10:2-5 and ultrasonically mixed.

2. A method for preparing the composite material with high specific capacity according to claim 1, characterized in that: The following steps are involved: (1) Using carbon spheres as templates, tetrahydrated cobalt acetate and tetrahydrated manganese acetate were used as cobalt and manganese sources, respectively, to prepare a mixed solution by a hydrothermal method. The mixed solution was centrifuged and washed with water for multiple times, dried, and calcined in an air atmosphere to obtain Co2MnO 4.5 Hollow nanospheres; the mass ratio of cobalt acetate tetrahydrate to manganese acetate tetrahydrate is 1-1.1:1, and the mass ratio of manganese acetate tetrahydrate to carbon ball powder is 93.5:60, 92.5:60 or 85:60; (2) LiF is dissolved in hydrochloric acid to prepare an etching solution, Ti3AlC2 powder is slowly added to the etching solution, heated for reaction, centrifuged for washing, and freeze-dried to obtain Ti3C2 nanosheets; the slow addition time is 5-15 min, and the heating reaction is carried out at 30-40 °C for 24-36 h; (3) Co2MnO 4.5 The hollow nanospheres were ultrasonically mixed with MXene nanosheets and freeze-dried to obtain Co2MnO 4.5 @Ti3C2 composite material, Co2MnO 4.5 The hollow nanospheres and Ti3C2 nanosheets were added to the ethylene glycol solution in a mass ratio of 10:2-5 and ultrasonically mixed.

3. The method for preparing a composite material with high specific capacity according to claim 2, characterized in that: In step (1), the hydrothermal method is to react at 90-100°C for 7-8 hours.

4. The method for preparing a composite material with high specific capacity according to claim 2, characterized in that: In step (1), the drying is carried out at 70-80°C for 12-16 h, and the calcination is carried out at 450-500°C for 2-3 h.

5. The method for preparing a composite material with high specific capacity according to claim 2, characterized in that: In step (2), the solid-liquid ratio of LiF to hydrochloric acid is 80-100:1 mg / mL, and the mass ratio of LiF to Ti3AlC2 powder is 8:3-5.

6. The method for preparing a composite material with high specific capacity according to claim 2, characterized in that: In step (3), the ultrasonic mixing time is 1.5 to 3 h, and the ultrasonic mixing power is 180 to 250 W.

7. Use of the composite material with high specific capacity according to claim 1 in preparing supercapacitors.

Citation Information

Patent Citations

  • MnCo2O4.5 hollow nanospheres as well as preparation method and application thereof

    CN109052487A

  • Preparation method and application of foam nickel loaded MnCo2O4.5 / MXene composite nano material

    CN112233912A

  • CoMoO4 / Ti3C2 nano composite particle, and preparation method and application thereof

    CN112563038A